2006
DOI: 10.1007/s10433-006-0036-y
|View full text |Cite
|
Sign up to set email alerts
|

Marital disruptions and loss of support in later life: a longitudinal study of the United Kingdom

Abstract: Marital disruption (i.e. due to death, divorce or separation) at older ages is an important issue as it removes the usual primary source of help and support: a husband or wife. To date, few studies have investigated the support implications (both , here defined as perceived support and social embeddedness and, defined as use of domiciliary care services) of marital disruptions in later life. This issue needs addressing as widow(er)hood and divorce are increasingly occurring at older ages. Employing data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…This might be due to significant difference in marital status between older adults with dementia in the nursing home and home care. As suggested by other studies, absence of a partner creates insecurity and isolation to the other (Beal, 2006;Glaser, Tomassini, Racioppi, & Stuchbury, 2006;Thomopoulou, Thomopoulou, & Koutsouki, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…This might be due to significant difference in marital status between older adults with dementia in the nursing home and home care. As suggested by other studies, absence of a partner creates insecurity and isolation to the other (Beal, 2006;Glaser, Tomassini, Racioppi, & Stuchbury, 2006;Thomopoulou, Thomopoulou, & Koutsouki, 2010).…”
Section: Discussionmentioning
confidence: 78%
“…For example, loss of a spouse in later life increases the odds of turning to formal care services (Glaser et al . 2006). Processes of substitution may be at work in society in general, while it has also been argued that generous welfare allocation may help to increase rather than decrease the probability of family solidarity and exchange of help between generations (Künemund and Rein 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This will lower the care provided by children's spouses because the study has revealed a lower level of involvement of cohabiting spouses in the care of their parents-in-law. Recent research has also demonstrated the importance of divorce for intergenerational relationships both as it affects elderly parents (Glaser et al 2006; Kalmijn 2007) and affects children (Brody et al 1995; Dooghe 1992; Grundy 1995). There is a risk that divorce and remarriage will lead to less caring by children-in-law, but it is up to future research to test this presumption.…”
Section: Discussionmentioning
confidence: 99%